Seismicity and Tectonics of central Peru: The Pucallpa Nest - Centeno Moncada, Estela Juana (2023)
The spatial distribution of seismicity and tectonics in the central region of Peru is analyzed using information contained in the Seismic Catalog of the Geophysical Institute of Peru (IGP), period 2015-2022 (M ≥4.5), to propose a 3D geometry for the Nazca plate within the subduction process. The results show that, in the central region, the Nazca plate subducts with an approximate angle of 28°- 30° up to a depth of 120 km to then continue in a subhorizontal manner up to the distance of 700 km. Near the city of Pucallpa, the Nazca plate develops a resubduction process with an approximate angle of 28° to a depth of 200 km. The distribution of the stress axes P and T show the process of plate convergence in front of the coastal zone and the internal deformation of the Nazca plate below the continent. At the height of the city of Pucallpa, the increase of seismicity of intermediate focus and at depths between 120 and 200 km, defines an area known as Pucallpa Nest.